The dynamic modelling and control system of a tethered aerostat for remote sensing applications - Fourie, Daniel Andries (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2009.